ENGLISH-MEDIUM INSTRUCTION AND MULTILINGUAL REALITIES: INTERNATIONAL STUDENTS’ VOICES FROM EMI CLASSROOMS IN INDONESIA - Sabiru Salihu; Zuliati Rohmah; Syariful Muttaqin; Siti Maftuhah Damio (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
English-medium instruction is expanding in Indonesian universities to support internationalization and global partnerships, yet classroom communication often remains multilingual. These multilingual realities matter because they shape how international students access disciplinary content, join discussion, and build a sense of belonging. This study examined how lecturers’ language practices and peer language choices shape international students’ participation and inclusion across EMI programs in Indonesia. Using a qualitative descriptive design, nine international students from Africa, Asia, and Europe at a university in East Java were purposely sampled; all had completed at least one semester of EMI experience. Semi-structured interviews were conducted and data were analyzed thematically following Braun and Clarke’s (2006) six-phase approach. Participants reported variability in lecturers’ English proficiency and intelligibility, especially early on when accents felt unfamiliar. They described routine code-switching between English and Bahasa Indonesia and mixed-language slides and handouts, which added translation work and sometimes obscured instructions. Peer talks frequently shifted to Bahasa Indonesia during group tasks and informal interaction, producing moments of micro-exclusion whereby some students remained silent or required translation. Students also relied on peers and digital translation tools, though these were limited by rapid speech and local abbreviations. Overall, EMI in this setting functioned as a hybrid language space rather than a stable English-only environment. Universities can respond by strengthening lecturer development for clear, accessible English, aligning materials with the stated medium, and providing structured peer support and guided digital language assistance to reduce routine barriers for international students and provide early orientation to local academic languages.